Nursing supervised practice in primary health care: dialogical planning as a device of the teaching-learning process - Claudia Mara de Melo Tavares; Lília Marques Simões Rodrigues (Rev Rene)
The study aims to analyze the dialogical planning of the Nursing Supervised Practice in Primary Care as a change device in nursing education. Based on the curriculum guidelines and the policies of health training promotion, it is estimated that the apprenticeship in primary care contributes to the formation of the critical- reflective profile of nurses. A qualitative descriptive study whose data collection happened through a questionnaire applied to ten teachers and ten primary care preceptors, from September to October 2011. Data were organized by the method of thematic content analysis and describe the practice occurs from a dialogical planning, includes assistance and educational projects and user demands. We verified little active performance of teachers and preceptors to design innovative processes. We conclude that dialogical planning promotes interaction between teaching and service and that the lack of innovative processes hinders the formation of the critical-reflective professional.